2021
DOI: 10.3390/ani11113192
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Dynamics of Changes in Table Eggs during Storage to Predict the Age of Eggs Based on Selected Quality Traits

Abstract: The aim of the study was to determine daily changes in some egg quality parameters, indirectly reflecting egg freshness, and to assess the possibility of predicting time from laying using mathematical methods. The study material consisted of 365 table eggs of medium (M, ≥53 g and <63 g) and large (L, ≥63 g and <73 g) weight classes (commercial stock, cage system, brown-shelled eggs) collected on the same day. Eggs were numbered individually and placed on transport trays and stored (14 °C, 70% RH). Every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…In the presented study, a very rapid increase in albumen pH during the storage of eggs was observed, followed by a gradual, slow decrease. Our findings correspond with those of other authors ( Itoh et al, 1981 ; Imai et al, 1986 ; Scott and Silversides, 2000 ; Jones and Musgrove, 2005 ; Nowaczewski et al, 2010a ; 2010b ; Aygun and Sert, 2013 ; Akpinar et al, 2015 ; Adamski et al, 2017 ; Ondrušíková et al, 2018 ; Taha et al, 2019 ; Brodacki et al, 2019 ; Drabik et al, 2021 ; Northcutt et al 2022 ). In our study, storage time significantly affected SW with a decrease and EST with a slight increase, but only for the F33 strain.…”
Section: Discussionsupporting
confidence: 94%
“…In the presented study, a very rapid increase in albumen pH during the storage of eggs was observed, followed by a gradual, slow decrease. Our findings correspond with those of other authors ( Itoh et al, 1981 ; Imai et al, 1986 ; Scott and Silversides, 2000 ; Jones and Musgrove, 2005 ; Nowaczewski et al, 2010a ; 2010b ; Aygun and Sert, 2013 ; Akpinar et al, 2015 ; Adamski et al, 2017 ; Ondrušíková et al, 2018 ; Taha et al, 2019 ; Brodacki et al, 2019 ; Drabik et al, 2021 ; Northcutt et al 2022 ). In our study, storage time significantly affected SW with a decrease and EST with a slight increase, but only for the F33 strain.…”
Section: Discussionsupporting
confidence: 94%
“…The increase in vitelline membrane permeability with time may have caused changes in yolk quality characteristics. Similar results have been reported in other studies depending on the time storage period (Drabik et al, 2021;Tabib et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…In that study, h was more than tripled when stored at 25 °C for 35 days. A similar increase in h was noted in the studies of Ragni et al (2007) and Ragni et al (2010) after 16 days of storage, as well as Drabik et al (2021) who examined this relationship during 35 days of storage of chicken eggs.…”
Section: Air Cell Dimensionssupporting
confidence: 72%